Avaliação nutricional da farinha de resíduos da indústria de filetagem de tilápias na alimentação de frangos de corte - Eyng, Cinthia (2009)
Three experiments were carried out aimed to nutricional evaluation of meal from tilapia filleting industrial waste (TM) in broiler chickens feeding. On the first experiment the chemical composition, apparent metabolizable energy (AME), corrected apparent energy (AMEn) and it s coefficients of metabolizability were determined. The total excreta collecting method was used to determinate the energy values, where 60 broiler chicken Cobb, aging 22 days, were shared in a completely randomized design, with six replications and five birds per experimental unit. According to the chemical composition results of TM, it depends of fish specie and meal production process. The AME, AMEn, CAME and CAMEn values to TM were: 3.733 kcal/kg, 3.082 kcal/kg, 78,13 e 64,50, respectively. On the second experiment, the true digestibility coefficients and the values of true amino acid digestibility of TM were determined in cecectomized roosters by the forced feed method. The experiment was analyzed as a complete randomized design with one test ingredient (TM), one fast, six replicates and one rooster per experimental unit. The average values of essential and non essential true amino acids digestibility coefficients, in percentage, were as follows: 92,04 and 87,49. On the experiment III, the performance of broilers feeding with different inclusion levels of TM (0, 2, 4, 6 and 8%) was analyzed. Four hundred and eighty day-old chicks were used in a completely randomized design with five treatments, six replicates and sixteen birds per experimental unit. Weight gain, final weight, feed intake, feed conversion and mortality from 1 to 21 days and 1 to 42 days of age were evaluated. In the end of experimental period the blood parameters (calcium, phosphorus, triglycerides), carcass, breast, thigh, drumstick, wing yield, liver relative weight and percentage of abdominal fat were calculated. Protein and fat deposition rate in breast and legs (thigh/drumstick) were determined. Forty five not trained tasters were used to sensorial analysis of meat. The samples were assessed using the nine-point structured hedonic scale for the characteristics: flavour, taste, color, texture and global quality. The experimental diet cost, economic efficiency index and cost index were calculated on analysis of economic viability. The data analyses showed difference (P<0,05) between inclusion levels of TM and the evaluate characteristics on 21 days of age. Despite of quadratic effect of treatments, the Linear Response Plateau (LRP) model provided the best data fit, the levels of inclusion were estimated in 2,10 and 2,02, which are the plato point for final weight and weight gain, respectively. The LRP was the only model that showed adjustment for feed intake and the level of inclusion was estimated in 1,86, which are the plato point. On the total period (1 to 42 days) the inclusion of 8% of TM in broiler chickens feeding did not affected performance, yield parameters, protein and fat deposition rate on carcass and sensorial quality of meat. Despite of linear increasing on blood triglycerides values, this level of inclusion reduced blood P and Ca values and provided the best economic efficiency.